2021
DOI: 10.3390/ijerph182010989
|View full text |Cite
|
Sign up to set email alerts
|

Snacking on Almonds Lowers Glycaemia and Energy Intake Compared to a Popular High-Carbohydrate Snack Food: An Acute Randomised Crossover Study

Abstract: Consuming nuts may have advantages over other snack foods for health and body-weight regulation. Suggested mechanisms include increased satiety and lower glycaemia. We used an acute randomised crossover trial to assess glycaemic and appetite responses to consuming two isocaloric snacks (providing 10% of participants’ total energy requirements or 1030 kJ (equivalent to 42.5 g almonds), whichever provided greater energy): raw almonds and sweet biscuits among 100 participants with available data (25 males and 75 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…After the removal of duplicate articles and excluded studies, 24 articles were identified as eligible. An additional 4 articles were identified after forward and backward citation searching, bringing the total number of articles included in this review to 28, derived from 27 studies [ 18 , 19 , 22 , 24 , 25 , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] ]. Figure 1 shows the study selection process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the removal of duplicate articles and excluded studies, 24 articles were identified as eligible. An additional 4 articles were identified after forward and backward citation searching, bringing the total number of articles included in this review to 28, derived from 27 studies [ 18 , 19 , 22 , 24 , 25 , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] ]. Figure 1 shows the study selection process.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, 2 studies [ 38 , 59 ] were excluded as they measured EE through methods other than indirect calorimetry: in this case, by estimating EE using physical activity records. There were 16 studies that reported energy compensation [ 18 , 38 , [40] , [41] , [42] , [43] , [45] , [46] , [47] , [48] , [50] , [51] , [52] , [53] , [54] , [55] ], 10 studies that reported EE [ 19 , 22 , 24 , 25 , 39 , 44 , 49 , [56] , [57] , [58] ], and 1 study (2 articles) that investigated both [ 36 , 37 ]. TABLE 1 , TABLE 2 present the characteristics of the energy compensation studies and EE studies, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In healthy individuals, the consumption of almonds with white bread was shown to significantly lower the postprandial area under the insulin concentration vs. time curve when compared to a high GI meal (instant mashed potatoes) (n = 15) [ 41 ] and significantly lower the glucose peak height when compared with white bread (n = 9) [ 27 ]. In another acute randomized crossover trial conducted in healthy participants (n = 100 with available data, n = 106 randomized), consumption of at least 10% of energy from raw almonds resulted in the mean area under the blood glucose response curve being significantly lowered when compared to consumption of biscuits [ 28 ]. Similar findings were shown for individuals at higher risk of diabetes.…”
Section: Effect Of Nut Consumption On Measures Of Glucose Metabolismmentioning
confidence: 99%
“…Short-term, acute/early phase satiety responses were measured over a 2-h period. Brown et al demonstrated that reduced energy intake occurred over 24 h and appetite effects may therefore need to be measured over a longer period [56]. In addition, future studies might consider standardising the evening meal and exercise the day before testing.…”
Section: Strengths and Limitationsmentioning
confidence: 99%